Long-term effects of soft rock amendment on changes of soil aggregate cementing agents of sandy soil by SEM-EDS - Sun, Zenghui; Liu, Zhe; Han, Jichang; Wang, Huanyuan; Zhang, Haiou; Yan, Jiakun (Frontiers in Environmental Science, 2023)
Soil aggregates are a crucial constituent of soil and have a significant function in regulating water, nutrients, air, and heat within the soil. The development of soil aggregates is influenced by various factors, including the soil's parent material and human activities. Understanding the formation and the mechanism of stabilization of soil aggregates is of great significance in the study of soil development, in regulating and managing organic carbon pools in soils, and in promoting soil fertility. In this study, aeolian sandy soil with a low degree of soil development and compound soil formed by combining soft rock and aeolian sandy soil were selected as the research objects. We selected three time points from 0 to 9 years after amendment by soft rock in order to investigate the changes of soil aggregate cementing agents. The shape of soil aggregates in both types of soils was analyzed by environmental scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), which were also used to assess the appearance of soil aggregates and quantify the composition of mineral elements on a cross section of the aggregate. The results show that when the soft rock and the aeolian sandy soil are compounded and mixed, the clay minerals in the soft rock change the microstructure of the original aeolian sandy soil from a single granular barrier to one characterized by a cumulative porous structure, indicating that clay minerals promote soil development and form aggregates with good structural properties. The cementing agents in the compounded soil aggregates are mainly clay minerals, aluminum, iron, and calcium. In comparison to aeolian sandy soils, the presence of iron and calcium in compounded soils is notably elevated. The iron oxides present in compounded soils serve a similar function to "bolts" in the formation of soil aggregates. These findings establish a theoretical foundation for investigating the process of soil aggregate formation and the mechanisms by which cementing agents contribute to their stabilization.